Representation Of Necrophilia On Carl O’Malley In Jorge Jaramillo’s Elena - Salsabila Adinda Oktavia; Hariyono (PT. Gudang Pustaka Cendekia, 2025)
The article focuses on the analysis of necrophilia on Carl O’Malley in Elena. The objective of the study are to find Representation of Necrophilia on Carl O’Malley in Jorge Jaramillo’s Elena. This article is a qualitative research. The types of Necrophilia in Jorge Jaramillo’s Elena found in the story are romantic and fetishistic necrophilia. Carl O’Malley experiences romantic necrophilia that is described as a denial that their lover already dead but they cannot cope and does not want to accept the truth. Carl also experiences fetishistics necrophilia that is described as a fetishistics motives of someone that usually take the whole body or just the specific parts of their body without a sexual intercourse.